Impact of growth factors and PTHrP on early and late chondrogenic differentiation of human mesenchymal stem cells - Weiss, Stefan; Hennig, Thea; Bock, Rosalie; Steck, Eric; Richter, Wiltrud (Journal of cellular physiology, 2010)
Common in vitro protocols for chondrogenesis of mesenchymal stem cells (MSCs) induce an inadequate, hypertrophic differentiation cascade reminiscent of endochondral bone formation. We aimed to modify chondrogenic protocols in order to identify potent inducers, promotors, and inhibitors to achieve better chondrogenesis. ...
Gesehen am 24.10.2023